Life sciences, society and policy (Springer-Verlag, GmbH, 2013)
"Life Sciences, Society and Policy is a peer-reviewed, Open Access journal devoted to fostering responsible innovation and sustainable development by providing an academic forum for engaged scholarship, interdisciplinary research, critical reflection and informed discussion concerning the ethical, social and legal dimensions of the life sciences, resulting in insights, tools and recommendations for civil society, policy, industry and education. Its aim is to analyze and assess the interrelatedness of emerging life sciences, society and policy."